Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Produktivitas Pegawai pada PD Gaya Hadjah Dick&Dick (Dodol Garut Hadjah) - Tatang Mulyana (Fakultas Ekonomi Universitas Garut, 2016)
The purpose of this study was to determine the effect of leadership and work environment on employee productivity at PD. Gaya Hadjah Dick&Dick (Dodol Garut Hadjah)”. The hypothesis used in this study is that there is an influence of leadership and work environment on employee productivity at PD. Gaya Hadjah Dick&Dick (Dodol Garut Hadjah)”. This research uses a descriptive method. The respondents in this study were 125 respondents. The analysis technique used in this study is multiple linear regression analysis using SPSS window 20.0. The partial test results show that leadership has an effect on employee productivity and the work environment has an effect on employee productivity. Furthermore, for simultaneous testing, it shows that leadership and work environment affect employee productivity at PD. Gaya Hadjah Dick&Dick (Dodol Garut Hadjah)”.